21st Century Skills Development in Secondary Schools: A Systematic Literature Review - Amri Amanulloh, Mochammad Ja'far; Marbun, Marlina; Sobri, Ahmad Yusuf; Ubaidillah, Aan Fardani (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2024)
This research aims to investigate the development of 21st-century skills in secondary schools and its implications for students' preparation in facing the increasingly complex demands of the modern era. In this research, 1395 papers were found on related topics and were filtered using PRISMA as a data filtering guide according to the research focus. With a focus on skills such as critical thinking, problem-solving, creativity, effective communication skills, and digital literacy, this research in-depth examines why developing 21st-century skills is so important in education today. This research also examines effective strategies and methods for integrating 21st-century skills into the educational process in secondary schools. The research results highlight the benefits of this approach in creating students who are ready to face a changing world and contribute to an increasingly complex and globally connected society. The results of this research will provide valuable insights for educators, school administrators, and policymakers in efforts to strengthen education in secondary schools to make it more relevant and effective in preparing students for a challenging future. The integration of 21st-century skills in secondary schools is a key step towards forming a future generation capable of adapting, innovating, and succeeding in an ever-changing environment.